2011
DOI: 10.1016/j.otsr.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Modified resection technique for proximal fibular osteochondromas

Abstract: Osteochondroma is one of the most common tumors arising from the proximal fibula. Surgical treatment of proximal fibula osteochondromas may vary from debulking to resection of proximal fibula. We describe a modified surgical technique for excision of proximal fibular osteochondromas which preserves the proximal tibio-fibular joint (PTFJ). We present a series of six cases of symptomatic proximal fibular osteochondroma. Four cases were solitary osteochondromas while two were a manifestation of a hereditary multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Type I excision defined by Malawer et al (7) was performed on 4 patients while type II excision was performed on 2 patients, modified excision defined by Mootha et al (8) was performed on 4 patients and above-knee amputation was performed on one patient in wide resection. Wide excision was performed on 3 diaphysis located ewing sarcoma cases and 2 metastasis ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I excision defined by Malawer et al (7) was performed on 4 patients while type II excision was performed on 2 patients, modified excision defined by Mootha et al (8) was performed on 4 patients and above-knee amputation was performed on one patient in wide resection. Wide excision was performed on 3 diaphysis located ewing sarcoma cases and 2 metastasis ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…One of these patients developed permanent drop foot since peroneal nerve was not protected due to tumor, the other three patients had complete recovery. Modified resection technique has been defined in fibula proximal zone osteochondroma in order to protect LCL (8). LCL reconstruction should be performed to prevent knee instability.…”
Section: Discussionmentioning
confidence: 99%
“…Any systematic study has not evaluated the role of arthrodesis of the proximal tibiofibular joint in knee stability and functional outcomes after resection of the proximal fibula. Most studies, in which type IV resection was included, reported that the arthrodesis of the proximal tibiofibular joint is not essential 16). Einoder and Choong17) also noted that wide resection of the fibular head for a tumor might not require reconstruction, unlike treatment of traumatic disruption of the lateral ligamentous structures of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Literature gives identical statistics and concludes that the proximal fibula is a common site for symptomatic Osteochondroma [2].…”
mentioning
confidence: 83%